(untitled) (Journal of Pathology of Nepal, 2019)
Mixed adenoneuroendocrine carcinoma is a rare tumor that is pathologically and clinically distinct from both its neuroendocrine and adenocarcinoma components. Confusion still exists regarding its histogenesis and therefore definite treatment protocol for its management has yet to be developed. Recent molecular characterization has been able to throw some light into the molecular profiles and mutations associated with the tumor. However, large scale studies are still to be carried out to unmask the true nature of this tumor. We report two cases of mixed adenoneuroendocrine carcinoma, one of the rectum and another of the sigmoid colon.